2022
DOI: 10.1111/jre.13078
|View full text |Cite
|
Sign up to set email alerts
|

Impact of periodontitis on gingival crevicular fluid miRNAs profiles associated with cardiovascular disease risk

Abstract: Background and Objective Recent emerging evidence has shown that microRNA (miRNAs) is involved in several epigenetic processes linked with periodontitis, increased oxidative stress and cardiovascular disease (CVD). The present study aimed to assess the impact of periodontitis on gingival crevicular fluid (GCF) miRNAs expression associated with CVD risk and to evaluate possible confounders that influenced this association. Materials and Methods For the present study, healthy controls (n = 28) and subjects with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 41 publications
1
62
0
1
Order By: Relevance
“…Early detection of these undiagnosed cases and monitoring the progressing periodontal disease can be easily achieved by the identification of key salivary biomarkers in gingivitis [ 5 ]. Besides, some key evidence has highlighted the moderating effects of micro RNAs (miRNAs) in periodontal tissue homeostasis and they have been linked to the release of proinflammatory cytokines in gingival fibroblasts throughout the initial stages of periodontitis, proposing the crucial modulatory role that miRNAs might have during the initiation and progression of the disease [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Early detection of these undiagnosed cases and monitoring the progressing periodontal disease can be easily achieved by the identification of key salivary biomarkers in gingivitis [ 5 ]. Besides, some key evidence has highlighted the moderating effects of micro RNAs (miRNAs) in periodontal tissue homeostasis and they have been linked to the release of proinflammatory cytokines in gingival fibroblasts throughout the initial stages of periodontitis, proposing the crucial modulatory role that miRNAs might have during the initiation and progression of the disease [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers evaluated the salivary acid uric level. Different studies showed that the salivary level of uric acid was lower in patients with periodontitis than in healthy patients [ 125 , 126 , 127 , 128 ]. Moreover, Priya et al [ 125 ] evaluated the salivary uric acid level variation after the non-surgical periodontal treatment.…”
Section: Studies Of Possible Biomarker For Periodontitismentioning
confidence: 99%
“…More specifcally, miRNA146a was found to be signifcantly upregulated in infamed gingival tissues and suppresses toll-like receptor-mediated nuclear factor-kappaB signaling pathway [50]. Isola et al demonstrated diferent gingival crevicular fuid (GCF) miRNA profle in periodontitis and cardiovascular disease (CVD) patients and highlighted GCF miRNA-21 may serve as a potential biomarker for both periodontitis and CVD [51]. Smoking, as a risk factor for periodontal disease, may infuence the disease causation and progression through dysregulating miRNAs expression.…”
Section: Onps and Periodontal Health: Inflammation Dysbiosis Bone Los...mentioning
confidence: 99%